Program Pengolahan Hasil Perkebunan Kelapa Sebagai Makanan Tambahan Atasi Stanting di Desa Teniga Kabupaten Lombok Utara - Yadnya, Made Sutha; Amalia , Serlyana; Jannah, Miftahul; Shahab, Seha; Sukmawati, Sukmawati; Noviana, Ena; Irawan , Aditia; Fiandra, Naufal Nanda; Nujulia, Nilti Haeratul; Solihati, Solihati; Putra, Doddy Setya Darsanti (Universitas Mataram, 2024)
Kuliah Kerja Nyata (KKN) Village Community Service (VCS) University of Mataram (UNRAM) has a main work program is the use of coconut products for the addition of nutrients. KKN VCS activities in Tenige Village, Tanjung District, North Lombok Regency are focused on overcoming stunting. KKN VCS UNRAM has the opportunity to provide innovations in improving agricultural yields such as innovating coconut yields. The target is for innovation in coconuts, as well as socialization of opportunities to make the production of Micro, Small and Medium Enterprises (MSMEs) in Tenige Village. The residents of Tenige Village can be independently moved to continue their business related to this processed product. Increasing the processing of coconut gizzards by processing them by making additional food containing eggs as a protein enhancer. Processed coconut products are made in the form of cakes called cookies of blondo which have a variant of high gisi content. Processing has been practiced and consumed by the people of Tenige Village. To maintain quality and quality, it was socialized with the help of UNRAM and sponsors in the form of speakers and financial assistance. Keywords: stunting; coconut; products; nutrients; Tenige Village